PENGARUH INTEGRITAS, KOMPETENSI, INDEPENDENSI, DAN MOTIVASI TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH (STUDI KASUS PADA INSPEKTORAT PEMERINTAH KOTA PANGKALPINANG) - Arpian, -; Wardhani, Rulyanti Susi (Journal of Accountancy FE UBB, 2013)
Influence of Integrity, Competence, Independence and Motivation Of the Quality of Audit in Financial Supervision Inspectorate Apparatus Area  (a Case Study on Government  Inspectorate Pangkalpinang city).The aim of this research is to find out the influence of integrity, competence, independence, and motivation of the quality of Audit in Financial Supervision  Inspectorate Apparatus Area.  The data used in this research is the primary data collected from offices of  Government Inspectorate Pangkalpinang city through the spread of the questions. Population in this research is all of Government Inspectorate Pangkalpinang city as the object of  research.  The technique of the  sample is a cencus or often called sampling saturates. A method of analysis of data in use in this research is of multiple of regression.From the results of the multiple regression analysis with significant levels of 5% obtained Independence and results in a partial  motivation and significant  positive impact on the quality of auditors in the financial control area, whereas the   integrity and competence of the variable has no effect. Simultaneously the four variables that affect the quality of free Auditors in the area of financial Supervision of 97,9% it means the fourth free variables in the model has posed a  considerable contribution to the quality of Auditors in the financial control area. Keywords: integrity, competence, independence, motivation and the quality of audits.